2017
DOI: 10.1093/jme/tjx182
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Temperature Range and Chikungunya Virus Infection in Invasive Mosquito Vectors

Abstract: Climate strongly influences the geographic distribution and timing of mosquito-borne disease outbreaks. Environmental temperature affects phenotypic traits of mosquitoes including vector competence for arboviruses mediated by changes in infection, extrinsic incubation period and in rates of transmission. Most experiments, however, are done at constant temperatures. In nature, mosquitoes are more likely to experience daily fluctuations in temperature. Here we compare disseminated infection (leg infection) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…Prediction of vector-borne disease spread remains difficult, as transmission of vector-borne disease is a dynamic, multifaceted system. This includes life traits of the mosquito, environmental factors, and vector-virus interactions [4,11,[39][40][41]. Here we demonstrate that mosquito age at the time of pathogen acquisition is a powerful driver of transmission potential due, in large part, to the age-dependence of daily mortality and biting habits.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Prediction of vector-borne disease spread remains difficult, as transmission of vector-borne disease is a dynamic, multifaceted system. This includes life traits of the mosquito, environmental factors, and vector-virus interactions [4,11,[39][40][41]. Here we demonstrate that mosquito age at the time of pathogen acquisition is a powerful driver of transmission potential due, in large part, to the age-dependence of daily mortality and biting habits.…”
Section: Discussionmentioning
confidence: 75%
“…Many things affect vector competence including vector species, discrete populations within species, and environmental factors [1, 14,19,20,28,40,42,43]. Several recent studies have focused on environmental factors such as temperature, and found that temperature not only affects vector competence of many arboviruses, especially in Aedes aegypti, but also several life traits of the mosquito [27,39,41]. This means that transmission is ultimately affected by the interactions of all of these temporally dependent processes, and while mathematical frameworks for assessing temperature and other extrinsic factors have been developed, they do not often explicitly consider age, another important temporal component to the transmission cycle of vector-borne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti [126,127,144,161–164,164–166], Ae. albopictus [127,144,162,164–167], Aedes terrens [168], and Haemagogus leucocelaenus [168] are all experimentally competent to transmit chikungunya virus. Chikungunya virus transmission in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies measured the effect of temperature on vector competence [145,161,162,171]. Adelman et al [161] found that under silenced RNAi conditions, Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation